Fighting arsenic at the grassroots: experience of BRAC's community awareness initiative in Bangladesh - Hadi, Abdullahel (BRAC Research and Evaluation Division (RED), 2019)
The study evaluates the arsenic mitigation project of BRAC in raising awareness of arsenic poisoning in rural communities in Bangladesh. Data came from selected project villages in south-western Bangladesh. Comparison villages were also selected from the same region. A total of 1240 randomly selected adults were interviewed in May 2000. Findings reveal that the mitigation project played a significant, positive role in raising awareness of the safe water options, signs of arsenicosis, mode of transmission and the type of treatment. Testing tube-well water for arsenic created curiosity, innovation and interest in the community, and the water treatment plant became a symbol of the arsenic campaign. The study concludes that the behavioral change aspects of the arsenic mitigation project have the potential to significantly improve the level of understanding about arsenic contamination in the traditional communities.